Investigation of indoor air quality determinants in a field study using three different data streams. (May 2019) - Thomas, Nirmala M.; Calderón, Leonardo; Senick, Jennifer; Sorensen-Allacci, MaryAnn; Plotnik, Deborah; Guo, Mengyang; Yu, Yi; Gong, Jie; Andrews, Clinton J.; Mainelis, Gediminas
Abstract: Indoor air quality (IAQ) is determined by indoor and outdoor sources and conditions, building characteristics, and occupant behavior. In the field study context where the researcher lacks full control of observational conditions, it is difficult to compare and integrate these determinants because they require such different types and sources of data. This pilot-level project investigated the potential to overcome these limitations by integrating traditional IAQ measurement techniques with questionnaires and analysis of building deficiencies using 3D infrared thermography imaging in two residential multi-apartment buildings. Of the building deficiencies detected by the 3D thermography, missing insulation (MI) correlated best with the IAQ measurements and questionnaire data. Apartments missing more than 5% of insulation in their exterior wall (n = 6) had a significantly higher number concentration of ultrafine airborne particles (diameter < 300 nm) (p = 0.013) and their indoor/outdoor ratio (p = 0.029) compared to apartments where less than 5% of insulation was missing (n = 14). The correlation was driven by apartments where no smoking or use candles or incense was reported. Ultrafine particle concentrations in apartments with combustion sources were higher regardless of the levels of MI. Corner apartments had a higher fraction of MI compared to non-corner apartments (p = 0.002); higher levels of MI were detected in apartments where a resident had an asthma attack in the past 12 months. Our data suggest that integration of different data streams produces a more informative IAQ investigation. This pilot-level study should be performed on a larger scale to examine its wider applicability in the IAQ field. Highlights: Building deficiencies detected by spatially resolved infrared thermography imaging. Missing insulation correlated with IAQ measurements and questionnaire data. Ultrafine particle concentration positively correlated with missing insulation levels. Indoor combustion sources positively correlated with airborne particle presence. Asthma attacks associated with high levels of missing insulation and indoor combustion sources.